2018
DOI: 10.7748/ncyp.2018.e1078
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ experiences of receiving an antenatal versus postnatal diagnosis of complex congenital heart disease

Abstract: Aim: To explore parents' experiences at the time of diagnosis of complex congenital heart disease (CHD) for their infant, and to compare whether experiences differ when receiving an antenatal versus postnatal diagnosis. Background: The time point at which parents receive a diagnosis of CHD has changed over the years due in part to advancements in fetal ultrasound; however, CHD still remains undiscovered until after birth in some cases. The psychological impact of time of diagnosis on parents' experiences has n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The research questions identified that informing parents of their child's condition, both pre-and postnatal, requires careful presentation of the diagnosis and its impact on the child's life. Studies concerning parental perspectives about being informed of an anomaly in their child have been widely studied (16)(17)(18)(19)(20) and recommendations for information strategies have been presented when a congenital anomaly is diagnosed prenatally (21) and postnatal (22). We identified that parents requested more holistic information about the diagnosis and the prognosis taking the child's abilities and future possibilities in consideration.…”
Section: Holistic and Empathic Communicationmentioning
confidence: 99%
“…The research questions identified that informing parents of their child's condition, both pre-and postnatal, requires careful presentation of the diagnosis and its impact on the child's life. Studies concerning parental perspectives about being informed of an anomaly in their child have been widely studied (16)(17)(18)(19)(20) and recommendations for information strategies have been presented when a congenital anomaly is diagnosed prenatally (21) and postnatal (22). We identified that parents requested more holistic information about the diagnosis and the prognosis taking the child's abilities and future possibilities in consideration.…”
Section: Holistic and Empathic Communicationmentioning
confidence: 99%
“…32 Prenatal diagnosis offers time for families to process and prepare for the birth of a child with a complex medical condition. [33][34][35][36] It is key, though, that this gift of time be used well, with appropriate medical evaluation, thorough prenatal counseling, and consultation with subspecialists as indicated; otherwise, prenatal diagnosis risks becoming "toxic knowledge" that only increases stress levels during pregnancy. 37 As noted, many parents recalled surprise, shock, and worry at the time of diagnosis, though on the quantitative DRS most parents indicated low levels of regret about the testing decisions they made during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Age in years at time of delivery, a median (range) 35 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) Age in years at time of interview, median (range) 37 (24-43)…”
Section: Parent Data (N = 17)mentioning
confidence: 99%
“…Previous studies reported that parents’ support groups, blogs, and websites are important sources of support for parents after receiving the diagnosis of congenital heart disease in a fetus. Medical professionals (physicians and nurses) were described as the main sources for information and reassurance [ 22 , 23 , 24 ]. Our findings can be explained by the limited time frame for recruiting participants for the study (2–4 weeks after the initial diagnosis).…”
Section: Discussionmentioning
confidence: 99%